Hermeneutika Al-Qur’an Amina Wadud - Ahmadiy Ahmadiy (Journal on Education, 2025)
In her book *"Women in the Qur'an"*, Amina Wadud attempts to make the interpretation of the Qur'an meaningful in the lives of women in the modern era. Interpretation here refers to the process of revisiting the words in the Qur'an and their context, in order to understand the true meaning of the Qur'anic text. Each interpretation seeks to convey the intent of the text, but at the same time, it also carries the prior context (perceptions, circumstances, background) of the person making the interpretation. Although each interpretation of a verse is unique, readers' understanding of the same verse may lead to different meanings.